2022
DOI: 10.3389/fendo.2022.975468
|View full text |Cite
|
Sign up to set email alerts
|

Association of long-term visit-to-visit variability of HbA1c and fasting glycemia with hypoglycemia in type 2 diabetes mellitus

Abstract: BackgroundSelf-management of blood glucose levels to avoid hypoglycemia is vital for patients with type 2 diabetes mellitus (T2DM). The association between specific metrics of glycemic variability (glycosylated hemoglobin A1c [HbA1c] and fasting plasma glucose [FPG]) and severe hypoglycemia has not been fully studied in patients with T2DM.MethodsIn this post hoc analysis, patients with established T2DM with a high risk of cardiovascular disease were included in the Action to Control Cardiovascular Risk in Diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…In contrast to previous studies, all participants in the ACCORD study had T2DM with CVD or a higher risk of CVD; thus, they had a higher risk of HF than previous studies ( 6 , 18 ). Therefore, our study might have had more power to detect an association between depressive symptoms and incidence of HF than previous studies.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In contrast to previous studies, all participants in the ACCORD study had T2DM with CVD or a higher risk of CVD; thus, they had a higher risk of HF than previous studies ( 6 , 18 ). Therefore, our study might have had more power to detect an association between depressive symptoms and incidence of HF than previous studies.…”
Section: Discussioncontrasting
confidence: 66%
“…Depression is also one of the most prevalent symptoms in patients with HF. Symptoms of depression worsen the quality of life and the prognosis of patients with established HF (6,7). However, it is unclear whether depression is a risk factor for HF or an incidental comorbidity of HF, due to different populations and instruments used to assess depressive symptoms (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The sustained long-term effects of a past hyperglycaemic period, entailed in the concept of metabolic memory and possibly mediated through epigenetic changes [ 39 ], might require a longer period spent in hyperglycaemia than that captured by short-term GV, which would intriguingly explain the distinct role of long-term GV as a risk factor. On the other hand, HbA 1c variability has been associated with a greater risk of severe hypoglycaemic events in individuals with type 2 diabetes [ 40 ]. Hypoglycaemia itself is proposed as a cardiovascular risk factor, possibly through hemodynamic changes, arrhythmias, and a combination of oxidative stress, endothelial dysfunction, inflammation and thrombosis, which seem to further increase in response to rebound hyperglycaemia [ 14 , 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the HbA 1C fluctuations observed in this study were relatively stable, and that lower HbA 1C variability in diabetic patients could potentially reduce or delay the occurrence of complications associated with diabetes ( 33 ). Moreover, lower levels of HbA 1C variability in patients could potentially reduce the number of hypoglycemic events, alleviate economic and psychological stress, and improve their quality of life ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among diabetic patients, HbA 1c variability is a risk factor for mortality and death due to cardiovascular disease ( 22 , 23 ), and it is independent of HbA 1c levels ( 24 ). In addition, numerous observational and randomized clinical trial studies have demonstrated that HbA 1c variability is linked to the risk of both microvascular and macrovascular complications in diabetes patients, as well as increased occurrences of hypoglycemia ( 12 , 19 , 25 27 ). Furthermore, a meta-analysis revealed that HbA 1c variability is connected with the incidence of dementia among diabetic patients ( 28 ).…”
Section: Introductionmentioning
confidence: 99%